Analisis Volume Penjualan Terhadap Laba Berdasarkan Artikel Terindeks Sinta 2017 – 2024 - Herdi Herdian Apriansyah; Nur Fitrianingsih; Rizka Salsabila Indri Priyadi; Susi Rahmawati; Rachmat Agus Santoso (CV. Ulil Albab Corp, 2024)
In its activities, companies try to maximize profits. This research aims to analyze the effect of sales volume on profits. This research method uses a literature review or literature review with a descriptive analysis approach to explore the relationship between sales volume and profits in articles indexed by Sinta between 2017-2024. The results of the analysis show that sales volume in the majority of companies is related to profits except in one case, namely in companies that have different business units from their main operations. The majority of articles that are related are articles indexed by Sinta 2, 3, and 5. On the other hand, articles that have found no relationship between sales volume and profit are articles indexed by Sinta 4. These articles carry out research on companies that carry out business activities. trading.